Durio gerikensis (Malvaceae), a new Arilless Durio from Hulu Perak, Malaysia - Ghazalli, Mohd Norfaizal; Hashim, Mohamad Hadrul; Besi, Edward Entalai; Mat-Esa, Muhammad Ikhwanuddin; Zaini, Ahmad Zaki; Saranum, Mohd Masri; Salleh, Salmaniza; Jajuli, Rosliza; Md Sah, Muhammad Shafie; Talip, Noraini; Latiff, A. (Phytotaxa, 2022)
A new species Durio gerikensis (Malvaceae) is described from Hulu Perak, Peninsular Malaysia, it can be easily recognised in the field by its reddish-pink flowers and small (6–7.5 cm in diameter), golden yellowish to pale yellow fruits with persistent calyx. It is unique from all the congeneric taxa by having two to four valved fruits with arilless seeds. Morphologically, Durio gerikensis is similar to D. lanceolatus Mast. (Masters 1875:499) and D. singaporensis Ridl. (Ridley 1916: 143) but they differ in their leaf, flower and fruit characteristics.